THE DEVELOPMENT OF ANIMATION-BASED PPKN TEACHING MATERIALS TO INCREASE LEARNING OUTCOME OF V-GRADE STUDENTS OF SD NEGERI 101927 SEKIP, LUBUK PAKAM DISTRICT - Aulia Rahman; Daulat Saragi; Yakobus Ndona (Sensei International Journal of Education and Linguistic, 2022)
This research was conducted based on the PPKn teaching materials used by teachers in learning that had not varied so that students tended to be passive and had an effect on student learning outcomes which were classified as low. This research was conducted with the aim of: (1) Produce animation-based Civics teaching materials in Class V SD Negeri 101927 Sekip, Lubuk Pakam District in accordance with KI and KD in the 2013 Curriculum, (2) Animation-based Civics teaching materials were able to increase students' interest and learning outcomes for Civics Education. class V SD Negeri 101927 Sekip, Lubuk Pakam District. The subjects of this study were students of class V SD Negeri 101927 Sekip, Lubuk Pakam District and as the object of the research were Civics teaching materials which were developed which produced products in the form of Animation-based Civics Modules. Researchers collected data using several instruments, namely learning outcomes tests, observations of teacher abilities and student response questionnaires. The animation-based Civics module is expected to be able to increase student activity in participating in Civics learning so that learning becomes more memorable and fun and has an effect on increasing Civics learning outcomes for fifth grade students at SD Negeri 101927 Sekip, Lubuk Pakam District.